Global Security Engagement: A New Model for Cooperative Threat Reduction - National Academy of Sciences (The National Academies Press, 2009)
The government's first Cooperative Threat Reduction (CTR) programs were created in 1991 to eliminate the former Soviet Union's nuclear, chemical, and other weapons and prevent their proliferation. The programs have accomplished a great deal: deactivating thousands of nuclear warheads, neutralizing chemical weapons, converting weapons facilities for peaceful use, and redirecting the work of former weapons scientists and engineers, among other efforts. Originally designed to deal with immediate post-Cold War challenges, the programs must be expanded to other regions and fundamentally redesigned as an active tool of foreign policy that can address contemporary threats from groups that are that are agile, networked, and adaptable. As requested by Congress, Global Security Engagement proposes how this goal can best be achieved. To meet the magnitude of new security challenges, particularly at the nexus of weapons of mass destruction and terrorism, Global Security Engagement recommends a new, more flexible, and responsive model that will draw on a broader range of partners than current programs have. The White House, working across the Executive Branch and with Congress, must lead this effort.

The Convergence of Infectious Diseases and Noncommunicable Diseases: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
On June 11 and June 12, 2019, the National Academies convened a workshop to explore the growing understanding of how the interplay between humans and microbes affects host physiology and causes noncommunicable diseases. Discussions included an overview of colliding epidemics, emerging research on associations between infectious and noncommunicable diseases, risks posed by chronic diseases to the development and severity of infectious diseases, and the influence of the microbiome. Workshop participants also examined the challenges and opportunities of convergence, the integration of health care delivery models and interventions, potential approaches for research, policy, and practice in the immediate-term, and potential directions for the long-term. This publication summarizes the presentations and discussions from the workshop.

Cooperative Threat Reduction Programs for the Next Ten Years and Beyond: Proceedings of a Symposium–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
The Cooperative Threat Reduction (CTR) Program was created by the United States after the dissolution of the Soviet Union to provide financial assistance and technical expertise to secure or eliminate nuclear weapons delivery systems; warheads, chemical weapons materials, biological weapons facilities, and nuclear, biological, and chemical weapons technology and expertise from the vast Soviet military complex. In a 2009 report, Global Security Engagement: A New Model for Cooperative Threat Reduction, the National Academy of Sciences (NAS) recommended adoption of a modified approach to thinking about CTR, including the expansion of CTR to other countries and specific modifications to CTR programs to better address the changing international security environment. On September 18-19, 2017, the NAS held a symposium to discuss the state of CTR and the future of CTR programs over the next 10 years and beyond. More than 120 participants and speakers met to share experience gained implementing CTR and to explore CTR in light of new developments in science and technology, such as the convergence of chemistry and biology, the life-sciences revolution, and the needs and interests of the scientific communities in different countries. Participants also considered how government CTR programs should change and\/or be reframed for the current and evolving global security and international political environment, as well as domestic requirements for impact and accountability. This publication summarizes the presentations and discussions from the workshop.

Developing Norms for the Provision of Biological Laboratories in Low-Resource Contexts: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
On June 27-28, 2018, the U.S. National Academies of Sciences, Engineering, and Medicine (the National Academies) convened an international workshop in Amsterdam, the Netherlands, on developing norms for the provision of laboratories in low-resource contexts. The U.S. Department of State's Biosecurity Engagement Program requested that the National Academies organize this workshop to engage an international group of organizations that provide funding for construction, upgrades, and maintenance of biological laboratories in countries without the means to build such labs themselves. Twenty-one people from 19 organizations participated. The intent was to advance the conversation about the identification and application of guiding principles and common norms for use by these organizations in their grants, partnerships, and aid. This publication summarizes the presentations and discussions from the workshop.

Countering Biological Threats: Challenges for the Department of Defense's Nonproliferation Program Beyond the Former Soviet Union - National Research Council (The National Academies Press, 2009)
In response to a request from the U.S. Congress, this book examines how the unique experience and extensive capabilities of the Department of Defense (DOD) can be extended to reduce the threat of bioterrorism within developing countries outside the former Soviet Union (FSU). During the past 12 years, DOD has invested 800 million in reducing the risk from bioterrorism with roots in the states of the FSU. The program's accomplishments are many fold. The risk of bioterrorism in other countries is too great for DOD not to be among the leaders in addressing threats beyond the FSU. Taking into account possible sensitivities about a U.S. military presence, DOD should engage interested governments in about ten developing countries outside the FSU in biological threat reduction programs during the next five years. Whenever possible, DOD should partner with other organizations that have well established humanitarian reputations in the countries of interest. For example, the U.S. Agency for International Development, the Centers for Disease Control and Prevention, and the World Health Organization should be considered as potential partners.

The Biological Threat Reduction Program of the Department of Defense: From Foreign Assistance to Sustainable Partnerships - National Research Council (The National Academies Press, 2007)
This Congressionally-mandated report identifies areas for further cooperation with Russia and other states of the former Soviet Union under the Cooperative Threat Reduction (CTR) program of the Department of Defense in the specific area of prevention of proliferation of biological weapons. The report reviews relevant U.S. government programs, and particularly the CTR program, and identifies approaches for overcoming obstacles to cooperation and for increasing the long-term impact of the program. It recommends strong support for continuation of the CTR program.

Global Infectious Disease Surveillance and Detection: Assessing the Challenges–Finding Solutions: Workshop Summary - Institute of Medicine
Early detection is essential to the control of emerging, reemerging, and novel infectious diseases, whether naturally occurring or intentionally introduced. Containing the spread of such diseases in a profoundly interconnected world requires active vigilance for signs of an outbreak, rapid recognition of its presence, and diagnosis of its microbial cause, in addition to strategies and resources for an appropriate and efficient response. Although these actions are often viewed in terms of human public health, they also challenge the plant and animal health communities. Surveillance, defined as \

Exploring Lessons Learned from a Century of Outbreaks: Readiness for 2030: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
In November 2018, an ad hoc planning committee at the National Academies of Sciences, Engineering, and Medicine planned two sister workshops held in Washington, DC, to examine the lessons from influenza pandemics and other major outbreaks, understand the extent to which the lessons have been learned, and discuss how they could be applied further to ensure that countries are sufficiently ready for future pandemics. This publication summarizes the presentations and discussions from both workshops.

Dual Use Research of Concern in the Life Sciences: Current Issues and Controversies - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
The potential misuse of advances in life sciences research is raising concerns about national security threats. Dual Use Research of Concern in the Life Sciences: Current Issues and Controversies examines the U.S. strategy for reducing biosecurity risks in life sciences research and considers mechanisms that would allow researchers to manage the dissemination of the results of research while mitigating the potential for harm to national security.

Governance of Dual Use Research in the Life Sciences: Advancing Global Consensus on Research Oversight: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Continuing advances in science and technology offer the promise of providing tools to meet global challenges in health, agriculture, the environment, and economic development; some of the benefits are already being realized. However, such advances have the potential to challenge the oversight systems for responsible conduct of life sciences research with dual use potential 2013 research that may have beneficial applications but that also could be misused to cause harm. Between June 10 and 13, 2018, more than 70 participants from 30 different countries and 5 international organizations took part in an international workshop, The Governance of Dual Use Research in the Life Sciences: Advancing Global Consensus on Research Oversight, to promote global dialogue and increased common understandings of the essential elements of governance for such research. Hosted by the Croatian Academy of Sciences and Arts in Zagreb, Croatia, the workshop was a collaboration among the InterAcademy Partnership, the Croatian Academy, the Croatian Society for Biosafety and Biosecurity, and the U.S. National Academies of Sciences, Engineering, and Medicine. This publication summarizes the presentations and discussions from the workshop.

Biosecurity Challenges of the Global Expansion of High-Containment Biological Laboratories: Summary of a Workshop - National Academy of Sciences; National Research Council (The National Academies Press, 2012)
During July 10-13, 2011, 68 participants from 32 countries gathered in Istanbul, Turkey for a workshop organized by the United States National Research Council on Anticipating Biosecurity Challenges of the Global Expansion of High-containment Biological Laboratories. The United States Department of State's Biosecurity Engagement Program sponsored the workshop, which was held in partnership with the Turkish Academy of Sciences. The international workshop examined biosafety and biosecurity issues related to the design, construction, maintenance, and operation of high-containment biological laboratories- equivalent to United States Centers for Disease Control and Prevention biological safety level 3 or 4 labs. Although these laboratories are needed to characterize highly dangerous human and animal pathogens, assist in disease surveillance, and produce vaccines, they are complex systems with inherent risks. Biosecurity Challenges of the Global Expansion of High-Containment Biological Laboratories summarizes the workshop discussion, which included the following topics: Technological options to meet diagnostic, research, and other goals; Laboratory construction and commissioning; Operational maintenance to provide sustainable capabilities, safety, and security; and Measures for encouraging a culture of responsible conduct. Workshop attendees described the history and current challenges they face in their individual laboratories. Speakers recounted steps they were taking to improve safety and security, from running training programs to implementing a variety of personnel reliability measures. Many also spoke about physical security, access controls, and monitoring pathogen inventories. Workshop participants also identified tensions in the field and suggested possible areas for action.

The Unique U.S.-Russian Relationship in Biological Science and Biotechnology: Recent Experience and Future Directions - National Research Council (The National Academies Press, 2013)
In the fall of 2010, the U.S. National Academies (consisting of the National Academy of Sciences, the National Academy of Engineering, and the Institute of Medicine) and the Russian Academy of Sciences (in cooperation with the Russian Academy of Medical Sciences and the Russian Academy of Agricultural Sciences) initiated a joint study of U.S.-Russian bilateral engagement in the biological sciences and biotechnology (hereinafter collectively referred to as bioengagement). The U.S. Department of State and the Russian Academy of Sciences provided support for the study. The academies established a joint committee of 12 leading scientists from the two countries to assess bioengagement activities since 1996 and to provide recommendations as to collaborative efforts in the near future. The Unique U.S.-Russian Relationship in Biological Science and Biotechnology: Recent Experience and Future Directions summarizes the principal conclusions and recommendations of the study.

Indo-U.S. Workshop on Challenges of Emerging Infections and Global Health Safety: Summary of a Workshop - National Academy of Sciences (The National Academies Press, 2016)
The United States and India have pledged to deepen the linkages between their people, their businesses, and their governments for the mutual benefit of both countries and for the promotion of global peace, stability, economic growth and prosperity. Both nations are now inclined to improve relations and cooperation, but the nations need specific actions that will yield progress and build confidence and momentum for further cooperation. The Indo-U.S. Workshop on Challenges of Emerging Infections and Global Health Safety, held in November 2014, encouraged scientists from both countries to examine global issues related to emerging and existing infections and global health safety, to share experience and approaches, and to identify opportunities for cooperation to improve practice and research in these areas. This report summarizes the presentations and discussions from the workshop.

Developing Capacities for Teaching Responsible Science in the MENA Region: Refashioning Scientific Dialogue - National Research Council (The National Academies Press, 2013)
Spurred on by new discoveries and rapid technological advances, the capacity for life science research is expanding across the globe2014and with it comes concerns about the unintended impacts of research on the physical and biological environment, human well-being, or the deliberate misuse of knowledge, tools, and techniques to cause harm. This report describes efforts to address dual use issues by developing institutes around the world that will help life sciences faculty learn to teach about the responsible conduct of science. Based on the successful National Academies Summer Institute for Undergraduate Biology Education and on previous NRC reports on effective methods for teaching about dual use issues, the report's authoring committee designed a general framework for the faculty institutes and chose the Middle East-North Africa (MENA) region to test a prototype faculty institute. In September 2012, the first Institute was held in Aqaba, Jordan, bringing together 28 participants from Algeria, Egypt, Jordan, Libya, and Yemen to engage with effective, evidence-based teaching methods, develop curricular materials for use in their own classrooms, and become community leaders on dual use and related topics. Developing Capacities for Teaching Responsible Science in the MENA Region: Refashioning Scientific Dialogue offers insights from the institute that will help in the design and implementation of future programs in the MENA region, and in other parts of the world.

Global Health Transitions and Sustainable Solutions: The Role of Partnerships: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
On June 13201314, 2018, the National Academies of Sciences, Engineering, and Medicine convened a multistakeholder workshop to examine the transitions affecting global health and innovative global health solutions. The goal of bringing these two topics together was to collectively explore models for innovative partnerships and private-sector engagement with the potential to support countries in transition. This publication summarizes the presentations and discussions from the workshop.

U.S.-Iran Engagement in Science, Engineering, and Health (2010-2016): A Resilient Program but an Uncertain Future - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
In 2010, the National Research Council published the report U.S-Iran Engagement in Science, Engineering, and Medicine (2000-2009). The review of the program described in detail the National Academies' science, technology, and health cooperation program carried out jointly with partners in Iran (otherwise known as science-engagement). The purpose of this new publication is to document the history and details of the National Academies' program of science-engagement from 2010 through 2016, while providing a perspective in considering future science-engagement. A variety of cooperative activities, and particularly workshops that dominated science-engagement during that period, are highlighted.

The Domestic and International Impacts of the 2009-H1N1 Influenza A Pandemic: Global Challenges, Global Solutions: Workshop Summary - Institute of Medicine
In March and early April 2009, a new, swine-origin 2009-H1N1 influenza A virus emerged in Mexico and the United States. During the first few weeks of surveillance, the virus spread by human-to-human transmission worldwide to over 30 countries. On June 11, 2009, the World Health Organization (WHO) raised the worldwide pandemic alert level to Phase 6 in response to the ongoing global spread of the novel influenza A (H1N1) virus. By October 30, 2009, the H1N1 influenza A had spread to 191 countries and resulted in 5,700 fatalities. A national emergency was declared in the United States and the swine flu joined SARS and the avian flu as pandemics of the 21st century. Vaccination is currently available, but in limited supply, and with a 60 percent effectiveness rate against the virus. The story of how this new influenza virus spread out of Mexico to other parts of North America and then on to Europe, the Far East, and now Australia and the Pacific Rim countries has its origins in the global interconnectedness of travel, trade, and tourism. Given the rapid spread of the virus, the international scientific, public health, security, and policy communities had to mobilize quickly to characterize this unique virus and address its potential effects. The World Health Organization and Centers for Disease Control have played critical roles in the surveillance, detection and responses to the H1N1 virus. The Domestic and International Impacts of the 2009-H1N1 Influenza A Pandemic: Global Challenges, Global Solutions aimed to examine the evolutionary origins of the H1N1 virus and evaluate its potential public health and socioeconomic consequences, while monitoring and mitigating the impact of a fast-moving pandemic. The rapporteurs for this workshop reported on the need for increased and geographically robust global influenza vaccine production capacities; enhanced and sustained interpandemic demand for seasonal influenza vaccines; clear \